2015
DOI: 10.1016/j.jeem.2015.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Directing technical change from fossil-fuel to renewable energy innovation: An application using firm-level patent data

Abstract: a b s t r a c tIn this paper we provide an analysis of directed technical change in the sector of electricity generation. We rely on patent data in fossil-fuel (FF) and renewable energy (REN) technologies for 5471 European firms over the 1978-2006 period. The novelty of our approach is in the focus on firm's heterogeneity in driving technological change. We make a distinction between small specialized firms, which innovate in only one type of technology, and large mixed firms, which innovate in both technologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(38 citation statements)
references
References 42 publications
0
38
0
Order By: Relevance
“…The gap between the patents in fossil fuel and renewable energy technology can be decreased through policies encouraging the market entrance of companies which are specialized in renewable technologies [34]. The integration degree between different technology classes of environmental patents is important to the environmental productivity performance of companies, as highlighted by Aldieri et al (2017) in the case of water pollution.…”
Section: Introductionmentioning
confidence: 99%
“…The gap between the patents in fossil fuel and renewable energy technology can be decreased through policies encouraging the market entrance of companies which are specialized in renewable technologies [34]. The integration degree between different technology classes of environmental patents is important to the environmental productivity performance of companies, as highlighted by Aldieri et al (2017) in the case of water pollution.…”
Section: Introductionmentioning
confidence: 99%
“…4 An additional mechanism has been identified by the literature about skills and technologies, in which design (along with engineering) has emerged as an important competence for mastering green technologies (Vona et al 2015): a result confirmed by firm-level patent analyses, showing that green innovators are firms operating in design-intensive activities (e.g. Noailly and Smeets 2015). Still though the use of patents, design has been suggested to be a strategic instrument to increase product complexity and thus the appropriability of the EI returns (Horbach, Oltra, and Belin 2013).…”
Section: Background Literaturementioning
confidence: 99%
“…The use of learning curves has been criticized for example by (Nordhaus, 2014) because correlation is not causation. However, in addition to the broader evidence above, Bettencourt, Trancik, & Kaur (2013) had already established that "growing markets have formed a vital complement to public R&D in driving innovative activity", and one of the most comprehensive subsequent studies (Noailly & Smeets, 2015), found that higher fossil fuel prices and increased renewable market size had both enhanced renewable innovation. All this is consistent with the evidence from patents.…”
Section: Evidence On Market-induced Innovation and Induced Cost Reducmentioning
confidence: 99%